Indonesian Cultural Diplomacy and Education in The Philippines in 2011-2019 - Ega Cahayati (Universitas Airlangga, 2022)
Education Diplomacy and Cultural Diplomacy has a strategic role in the public diplomacy of the Indonesian state. In the interaction of international relations, the formation of phenomena such as the partnership between various components of society has made the situation of the current global relations system increasingly colorful. It can also see that the role of diplomacy in this section is not inferior to the practice of public diplomacy adopted by the state. For example, in the field of education, the participation of scholars in the development of public diplomacy will accelerate the improvement of the quality of human resources in Indonesia and Filipina. This method of diplomacy can also be carried out through student exchange to the Philippines, art performances and cultural performances of the Indonesian state, discussions with lecturers & teachers, and much more. There is also uniqueness in implementing this diplomacy, such as cooperation, which leads to mutual benefit, respect, and appreciation. In addition, educational & cultural diplomacy can also provide new ideas. This unique idea leads to solving problems within the scope of international relations. Therefore, Indonesia must improve its cultural & educational Diplomacy in Filipina country.